Sisa Lebih Pembiayaan Anggaran Sebagai Pemoderasi Antara Dana Perimbangan, Dana Bagi Hasil, dan Pajak Daerah Terhadap Belanja Modal - Dirvi Surya Abbas; Savira Yenita Sari; Mohamad Zulman Hakim; Hesty Erviani Zulaecha; Dewi Rachmania (Universitas Kristen Maranatha, 2021)
Abstract This research aims to determine the effect of compensation funds, revenue-sharing funds and local taxes on capital expenditures in districts or cities in the province of Banten. Observation time in this research is for six years, namely 2015 to 2020. The object of observation in this study is all districts or cities in Banten Province. The sampling technique used is intentional (purposive) sampling. This study uses secondary data obtained from the Realization Report of the Regional Revenue and Expenditure Budget. The method of analysis used panel data regression analysis. The results of the research explain that the Balancing Fund has a negative and insignificant effect on capital expenditure, the Profit Sharing Fund has a negative and significant effect on capital expenditure, Regional Taxes have a positive and insignificant effect on capital expenditure, while the remaining excess budget financing has a negative and significant impact on Expenditures. Capital, Remaining Budget Financing is able to moderate and able to strengthen or weaken the relationship between Balancing Funds to Capital Expenditures, Remaining Budget Financing is able to moderate and able to strengthen the relationship between Profit Sharing Funds to Capital Expenditures, and Remaining Funding Budgets are unable to moderate and are unable to strengthen or weaken the relationship between Regional Taxes and Capital Expenditures. Keywords: Capital Expenditures, Balancing Funds, Profit Sharing Funds, Regional Taxes, and Remaining Budget Financing